(untitled) (Colombia Medica, 1989)
The clinical charts of 33 patients with anal fissure were revived between March 1986 and July 1988; 28 patients (85%) were treated with lateral subcutaneous internal anal sphincterotomy and 5 with anal stretching or lord procedure. The fissure was located in the posterior midline in 27 patients (82%), in the anterior midline in 3 (9%), and in the other patients, it was located laterally (3%). In none of such patients, concomitant inflammatory bowel disease was demonstrated. In 10 cases (30%), a complex of sentinel pile and hypertrophy of anal papilla was founded. In one of these, the histology of the sentinel pile resected revealed a squamous cell carcinoma in situ. The was a recurrence in one patient treated with anal stretching, with no recurrences noted in those treated with sphincterotomy. Infectious complications were demonstrated in 4 patients (12%). These cases were treated succesfully with drainage and curettage of the intersphincteric space. All patients were followed up for at least six months. No cases of anal incontinence, soiling, or delayed healing were demonstrated. Lateral subcutaneous internal anal sphincterotomy is an efficient and easy procedure for the treatment of chronic anal fissures. Our infectious rate was higher than the frequencies reported in other series. Because of this fact, we have been forced to depurate our surgical technique, especially if there is concomitant anal pathology, like fistula in ano or hemorrhoids. This circumstance makes morbidity higher if they are simultaneously treated with anal fissure.